Numerical investigation of seismic behavior of short-core all-steel buckling restrained braces. (November 2015) - Hoveidae, N.; Tremblay, R.; Rafezy, B.; Davaran, A.
Abstract: Conventional buckling restrained braces used in concentrically braced frames are expected to yield in both tension and compression without significant degradation of capacity under severe seismic ground motions. On the other hand, a new short core buckling restrained brace system could be introduced as an alternative for a conventional full core BRB. In a short core BRB (SCBRB), the core element is built shorter than usual. Therefore, for a given story drift, the core accepts bigger axial strains compared to a conventional (full core) BRB. A short core BRB seems to be easily fabricated, inspected, and replaced after a severe earthquake. The purpose of this study is to show how this type of buckling restrained braces is feasible. Reducing the core length in a buckling restrained brace may result in a shorter encasing member, decrease in frictional forces acting at the core and buckling restraining mechanism interface, and, as a consequence, reduction of the compression strength adjustment factor in the brace. This paper numerically investigates the seismic behavior of short core buckling restrained braced frames. The minimum core length of BRB is determined by considering the low cycle fatigue life of the core plate and the maximum anticipated strain demand under standard loading protocol. Nonlinear time history analyses were also performed on four and ten story prototype buildings equipped with full core (conventional BRBs) and short core BRBs and the story drifts were compared. The results showed that the SCBRB system is partially able to reduce the story and residual story drifts in the braced frames. In addition, SCBRBs sustain large plastic deformations without crossing the low cycle fatigue life borders or instability of the encasing system. However, the economic and practical aspects of using SCBRB seem to be more distinct in comparison to its mechanical characteristics. Highlights: Propose of a new type of all-steel buckling restrained braces called short-core buckling restrained brace. A minimum core length proposed for short-core BRBs. Numerical investigation of seismic behavior of short-core and full-core buckling restrained braces.